Possibilities and limits of use plastic constructions in fruit growing technologies - Gonda, I.; Vaszily, B.; Soltész, M. (International Journal of Horticultural Science, 2011)
On the Experimental Station Pallag of Debrecen University different combinations of fruit species and rootstocks have been raised under and without plastic foil cover in 2002. The growth and productivity of the grafts was our objective of comparison. Results revealed substantial differences in fruit set and yield depending on species and varieties. Sweet and sour cherry varieties grew much shorter under the plastic cover, whereas apricots, peaches and plums set fruit much more eagerly compared with the trees outside the plastic cover. Outside the plastic cover, the trees were much more developed at the beginning of their fruiting period. In spite of that, the growing processes were more intense under the foil. The differences are allegedly due to the repeated summer pruning necessary under the restricted space of the foil, on the other hand, due to the root concurrence because of the dense planting. Regarding the inner properties of the fruits, soluble solids, sugar and acids were higher outside, whereas macro- and mezzo-elements (P, K, Ca, Mg) were more abundant in fruits grown under the foil cover. Further efforts to explore those relations with other varieties and rootstocks are justified.